A study of residual physical disability after a burn injury in patients admitted in tertiary care hospitals in Karnataka, India - Gowri Shankar; Vijaya A Naik (Wolters Kluwer Medknow Publications, 2016)
Introduction: Burn Injuries Are Among The Leading Causes Of Disability-Adjusted Life Years Lost In Low And Middle Income Countries. In India, About 6-7 Million People Suffer From Burn Injuries Every Year. Out Of Them, 7 Lakh Require Hospital Admission And 2.4 Lakh Become Disabled. Materials And Methods: A Prospective Study Was Conducted To Identify The Epidemiological Determinants For Residual Physical Disabilities In Burn Patients Admitted Between April 1St, 2004 And March 31St, 2005 In Two Tertiary Hospitals In Belagavi City, Karnataka, India. Out Of 316 Patients Admitted During The Study Period, 48 (15.19%) Had Residual Physical Disability At The Time Of Discharge. Data About Their Socio Demographic Profile, Total Burn Surface Area, Mode And Type Of Burn, Severity And Depth Of Burn And Type Of Disability Was Collected On A Pre Designed Proforma After Informed Consent. Data Was Analyzed By Percentages And Chi-Square Test. Results: Out Of 48 Patients With Residual Physical Disability Sustained After A Burn Injury, 15 (31.25%) Were Males And 33 (68.75%) Were Females. Maximum Number (70.83%) Were Between 15-44 Years Of Age. Majority (77.08%) Were From Rural Areas. It Was Observed That 62.5% Were Wearing Synthetic Clothes At The Time Of Burn. Majority (85.4%) Had Scar Contractures. Maximum Number (89.58%) Had Upper Limb Injury Followed By 47.9% With Chest Injury. Conclusion: Burn Injury Should Be Prevented At All Costs And Health Education Regarding Safety Measures Should Be Implemented In All Educational Institutions.